A solid powder additive for flue gas desulfurization and preparation method thereof

Through high-temperature calcination of composite adsorbent and magnesium oxide and coating treatment of magnesium hydroxide, a solid powder additive for flue gas desulfurization was prepared, which solved the problems of low reaction activity, high energy consumption and poor stability in the prior art, and achieved efficient flue gas desulfurization effect.

CN119406189BActive Publication Date: 2025-04-18SHANDONG CHANGQING NANO MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510021538.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-18
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing flue gas desulfurization process has problems such as low reaction activity, high energy consumption and poor stability, and it is difficult to meet the strict emission standards requirements, and the desulfurization efficiency cannot meet production requirements.

Method used

A solid powder additive for flue gas desulfurization was prepared by composite adsorbent from activated carbon and zeolite, and calcined with magnesium oxide at high temperature, combined with magnesium hydroxide coating treatment.

Benefits of technology

By increasing the contact area between flue gas and solid powder additives, the efficiency of flue gas desulfurization is improved, and the acidic substances and sulfides in the flue gas can be effectively removed, thereby improving the overall performance of the desulfurization system.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of flue gas desulfurization, and specifically discloses a solid powder additive for flue gas desulfurization and a preparation method thereof. A solid powder additive for flue gas desulfurization and a preparation method thereof include the following steps: (1) Preparation of a composite adsorbent: Grind and mix activated carbon and zeolite, add sodium carboxymethyl cellulose and polyvinyl alcohol, stir until uniform, dry, extrude and form, and heat treat at 200-250°C for 1-1.2h to obtain a composite adsorbent; (2) Heat treatment: Grind and mix the composite adsorbent and magnesium oxide, and perform high-temperature calcination at 700-850°C for 1-2h to obtain a mixed powder; (3) Post-treatment: The mixed powder is coated with magnesium hydroxide to obtain a solid powder additive; In addition, the preparation method of the present application has the advantage of improving the efficiency of flue gas desulfurization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of flue gas desulfurization, and more specifically, to a solid powder additive for flue gas desulfurization and a preparation method thereof. Background Art

[0002] At present, coal-fired power plants and heavy industrial facilities generally use wet flue gas desulfurization technology to remove sulfur dioxide from flue gas. This technology has played an important role in reducing air pollution and improving environmental quality. In recent years, with the continuous improvement of global requirements for environmental pollution control, countries have introduced more stringent emission standards, which has promoted the continuous innovation and development of desulfurization technology. In this context, exploring new, efficient and economical desulfurization technologies and methods has become an urgent task in the field of environmental protection and chemical industry.

[0003] In the existing flue gas desulfurization process, the efficiency of flue gas desulfurization is often improved by adding catalysts, adjusting reaction conditions, improving absorbents, etc. Although the desulfurization efficiency has been improved to a certain extent, there are still problems such as low reaction activity, high energy consumption, and poor stability. Especially in large-scale industrial applications, these problems are more prominent, resulting in the overall performance of the desulfurization system failing to achieve the expected goals, making it difficult to meet strict emission standards, and the desulfurization efficiency failing to meet production needs. Summary of the invention

[0004] In order to improve the efficiency of flue gas desulfurization, the present application provides a solid powder additive for flue gas desulfurization and a preparation method thereof.

[0005] In a first aspect, the present application provides a method for preparing a solid powder additive for flue gas desulfurization, using the following technical solution:

[0006] A method for preparing a solid powder additive for flue gas desulfurization comprises the following steps:

[0007] (1) Preparation of composite adsorbent: After grinding and mixing activated carbon and zeolite, sodium carboxymethyl cellulose and polyvinyl alcohol are added, stirred until uniform, dried, extruded, and heat treated at 200-250°C for 1-1.2h to obtain a composite adsorbent;

[0008] (2) Heat treatment: Grind and mix the composite adsorbent and magnesium oxide, and perform high-temperature calcination at a temperature of 700-850°C for 1-2 hours to obtain a mixed powder;

[0009] (3) Post-treatment: The mixed powder is coated with magnesium hydroxide to obtain a solid powder additive.

[0010] By adopting the above technical scheme, the composite adsorbent is formed by a composite of activated carbon and zeolite, has a large specific surface area, can effectively increase the contact area between the flue gas and the solid powder additive, thereby improving the efficiency of flue gas desulfurization, magnesium oxide is a highly alkaline compound, has a strong acid gas absorption capacity, can be with acidic substances in the flue gas, such as sulfur dioxide, sulfur trioxide, etc., high-temperature calcination of magnesium oxide and the composite adsorbent can make the two better combined, absorb and react with sulfur-containing substances in the flue gas, and desulfurize the flue gas, magnesium hydroxide can react with sulfides and various toxic substances in the flue gas, and the mixed powder is coated with magnesium hydroxide, which can further improve the desulfurization capacity of the solid powder additive.

[0011] Preferably, the activated carbon is treated as follows before being mixed with the zeolite: the activated carbon is dried at 100-105°C for 24 hours, nitrogen is introduced, the temperature is raised to 450-500°C and kept for 1 hour, and then cooled to room temperature.

[0012] By adopting the above technical solution, the activated carbon is activated at high temperature under the action of nitrogen, which can remove impurities in the pores of the activated carbon and regulate the specific surface area of ​​the activated carbon, thereby improving the adsorption performance of the activated carbon.

[0013] Preferably, the mass ratio of the composite adsorbent to magnesium oxide is (0.4-0.6):(0.4-0.6), and the mass ratio of activated carbon to zeolite is (1-1.2):(0.9-1.1).

[0014] By adopting the above technical scheme, the mass ratio of the composite adsorbent to magnesium oxide is controlled, so that the solid powder additive can better adsorb and contact the flue gas and react with the sulfides and harmful substances in the flue gas. The mass ratio of activated carbon to zeolite is controlled, so that the composite adsorbent has the best adsorption effect on the flue gas, and the contact area between the solid powder additive and the flue gas is increased.

[0015] Preferably, in the post-treatment, the step of coating the mixed powder with magnesium hydroxide is: adding the mixed powder to an alcohol aqueous solution of magnesium chloride, adding a dispersant, ultrasonically shaking for 30 minutes, adding an alcohol aqueous solution of sodium hydroxide at 60° C. while stirring, and after the addition is completed, stirring and reacting for 18 hours, washing, and drying.

[0016] By adopting the above technical scheme, the mixed powder is mixed with an alcohol aqueous solution of magnesium chloride, and then fully dispersed by ultrasound. After sodium hydroxide is added, the generated magnesium hydroxide is gradually deposited on the surface of the mixed powder, so that the surface of the mixed powder is coated with a layer of magnesium hydroxide. The magnesium hydroxide can react with the acidic substances in the flue gas, thereby effectively removing the sulfide in the flue gas.

[0017] Preferably, the mass ratio of the mixed powder to magnesium chloride is (1.3-1.7):(4.4-4.9).

[0018] By adopting the above technical solution, the mass ratio of the mixed powder to magnesium chloride is controlled, thereby controlling the deposition amount of magnesium hydroxide on the surface of the mixed powder, so that the magnesium hydroxide can be fully deposited and coated evenly, effectively improving the desulfurization performance of the solid powder additive.

[0019] Preferably, the post-treatment further comprises the following steps: dissolving polyethyleneimine and urea in water to form a mixed solution, heating and boiling for 2 hours, adding the mixed powder coated with magnesium hydroxide to the mixed solution, stirring for 72 hours, filtering, washing and drying.

[0020] By adopting the above technical scheme, polyethyleneimine and urea can react to form urea-based polymers, which are loaded on the surface of the mixed powder, and amino groups are introduced into the mixed powder. The amino groups can react and fix with sulfides in the flue gas, thereby improving the desulfurization efficiency and capacity of the solid powder additive.

[0021] Preferably, the mass ratio of polyethyleneimine to urea is (4.9-5.2):(0.8-1.2).

[0022] By adopting the above technical solution, the mass ratio of polyethyleneimine and urea is controlled, so that polyethyleneimine can be better bonded with urea, the decomposition and volatilization of urea are reduced, the amino content in the solid powder additive is increased, and the desulfurization efficiency and capacity of the solid powder additive are enhanced.

[0023] In a second aspect, the present application provides a solid powder additive for flue gas desulfurization, which adopts the following technical solution:

[0024] A solid powder additive for flue gas desulfurization is prepared by using a preparation method of a solid powder additive for flue gas desulfurization.

[0025] By adopting the above technical solution, the prepared solid powder additive has good stability and can desulfurize flue gas with high efficiency.

[0026] In summary, this application has the following beneficial effects:

[0027] 1. The composite adsorbent in the present application is formed by a composite of activated carbon and zeolite, has a large specific surface area, can effectively increase the contact area between the flue gas and the solid powder additive, thereby improving the efficiency of flue gas desulfurization, magnesium oxide is a highly alkaline compound, has a strong acid gas absorption capacity, can be with acidic substances in the flue gas, such as sulfur dioxide, sulfur trioxide, etc., high-temperature calcination of magnesium oxide and the composite adsorbent can make the two better combined, absorb and react with sulfur-containing substances in the flue gas, desulfurize the flue gas, magnesium hydroxide can react with sulfides and various toxic substances in the flue gas, and the mixed powder is coated with magnesium hydroxide, which can further improve the desulfurization capacity of the solid powder additive.

[0028] 2. In this application, the mass ratio of the composite adsorbent to magnesium oxide is controlled so that the solid powder additive can better adsorb and contact the flue gas and react with the sulfides and harmful substances in the flue gas. The mass ratio of activated carbon to zeolite is controlled so that the composite adsorbent has the best adsorption effect on the flue gas and increases the contact area between the solid powder additive and the flue gas.

[0029] 3. In the present application, the mixed powder is mixed with an alcohol aqueous solution of magnesium chloride, and then fully dispersed by ultrasound. After sodium hydroxide is added, the generated magnesium hydroxide is gradually deposited on the surface of the mixed powder, so that the surface of the mixed powder is coated with a layer of magnesium hydroxide. The magnesium hydroxide can react with the acidic substances in the flue gas, thereby effectively removing the sulfide in the flue gas. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments. Example

[0031] Example 1

[0032] A method for preparing a solid powder additive for flue gas desulfurization comprises the following steps:

[0033] (1) Preparation of composite adsorbent: After grinding and mixing activated carbon and zeolite in a mass ratio of 1:0.9, sodium carboxymethyl cellulose and polyvinyl alcohol were added, wherein the amount of sodium carboxymethyl cellulose added was 8.1wt% of the total amount of the composite adsorbent, and the amount of polyvinyl alcohol added was 5.9wt% of the total amount of the composite adsorbent. After stirring until uniform, the mixture was dried, extruded, and heat treated at 200°C for 1.2h to obtain a composite adsorbent.

[0034] (2) Heat treatment: the composite adsorbent and magnesium oxide were ground and mixed in a mass ratio of 0.4:0.6, and calcined at 850°C for 2 h to obtain a mixed powder;

[0035] (3) Post-treatment: Add the mixed powder to 50 mL of 0.8 mol / L magnesium chloride alcohol aqueous solution, with the mass ratio of the mixed powder to magnesium chloride being 1.3:4.4, add dispersant OP-10, and perform ultrasonic vibration for 30 min. Add 50 mL of 1.6 mol / L sodium hydroxide alcohol aqueous solution at 60 °C while stirring. After the addition is completed, stir and react for 18 h, wash and dry to obtain a solid powder additive.

[0036] Example 2

[0037] A method for preparing a solid powder additive for flue gas desulfurization comprises the following steps:

[0038] (1) Preparation of composite adsorbent: After grinding and mixing activated carbon and zeolite in a mass ratio of 1.2:1.1, sodium carboxymethyl cellulose and polyvinyl alcohol were added, wherein the amount of sodium carboxymethyl cellulose added was 9.6wt% of the total amount of the composite adsorbent, and the amount of polyvinyl alcohol added was 4.2wt% of the total amount of the composite adsorbent. After stirring until uniform, the mixture was dried, extruded, and heat treated at 250°C for 1h to obtain a composite adsorbent.

[0039] (2) Heat treatment: The composite adsorbent and magnesium oxide were ground and mixed in a mass ratio of 0.6:0.4, and calcined at 700°C for 2 hours to obtain a mixed powder;

[0040] (3) Post-treatment: Add the mixed powder to 50 mL of 0.55 mol / L magnesium chloride alcohol aqueous solution, with the mass ratio of the mixed powder to magnesium chloride being 1.7:4.9, add dispersant OP-10, and perform ultrasonic vibration for 30 min. Add 50 mL of 1.1 mol / L sodium hydroxide alcohol aqueous solution at 60 °C while stirring. After the addition is completed, stir and react for 18 h, wash and dry to obtain a solid powder additive.

[0041] Example 3

[0042] A method for preparing a solid powder additive for flue gas desulfurization comprises the following steps:

[0043] (1) Preparation of composite adsorbent: After grinding and mixing activated carbon and zeolite in a mass ratio of 0.5:0.5, sodium carboxymethyl cellulose and polyvinyl alcohol were added, wherein the amount of sodium carboxymethyl cellulose added was 8.6wt% of the total amount of the composite adsorbent, and the amount of polyvinyl alcohol added was 4.5wt% of the total amount of the composite adsorbent. After stirring until uniform, the mixture was dried, extruded, and heat treated at 250°C for 1.2h to obtain a composite adsorbent.

[0044] (2) Heat treatment: Grind and mix the composite adsorbent and magnesium oxide in a mass ratio of 5:1.1, and perform high-temperature calcination at a temperature of 700-850°C for 1-2h to obtain a mixed powder;

[0045] (3) Post-treatment: Add the mixed powder to 50 mL of 0.5 mol / L magnesium chloride alcohol aqueous solution, with the mass ratio of the mixed powder to magnesium chloride being 1.5:4.6, add dispersant OP-10, and perform ultrasonic vibration for 30 min. Add 50 mL of 1 mol / L sodium hydroxide alcohol aqueous solution at 60 °C while stirring. After the addition is completed, stir and react for 18 h, wash and dry to obtain a solid powder additive.

[0046] Example 4

[0047] The difference between Example 4 and Example 1 is that in Example 4, the activated carbon is subjected to the following treatment before being mixed with the zeolite: the activated carbon is dried at 100°C for 24 hours, nitrogen is introduced, the temperature is raised to 450°C and kept for 1 hour, and then cooled to room temperature.

[0048] Example 5

[0049] The difference between Example 5 and Example 1 is that in Example 5, the activated carbon is subjected to the following treatment before being mixed with the zeolite: the activated carbon is dried at 105°C for 24 hours, nitrogen is introduced, the temperature is raised to 500°C and kept for 1 hour, and then cooled to room temperature.

[0050] Example 6

[0051] The difference between Example 6 and Example 1 is that in Example 6, the mass ratio of the composite adsorbent to magnesium oxide is 0.4:0.2.

[0052] Example 7

[0053] The difference between Example 7 and Example 1 is that in Example 7, the mass ratio of the composite adsorbent to magnesium oxide is 0.4:1.

[0054] Example 8

[0055] The difference between Example 8 and Example 1 is that in Example 8, the mass ratio of activated carbon to zeolite is 1:0.5.

[0056] Example 9

[0057] The difference between Example 9 and Example 1 is that in Example 9, the mass ratio of activated carbon to zeolite is 1:1.7.

[0058] Example 10

[0059] The difference between Example 10 and Example 1 is that in Example 10, the mass ratio of the mixed powder to magnesium chloride is 1.3:3.1.

[0060] Embodiment 11

[0061] The difference between Example 11 and Example 1 is that in Example 11, the mass ratio of the mixed powder to magnesium chloride is 1.3:5.9.

[0062] Example 12

[0063] The difference between Example 12 and Example 1 is that in Example 12, the post-treatment also includes the following steps: dissolving 2.2 g of polyethyleneimine and urea in 45 mL of water to form a mixed solution, the mass ratio of polyethyleneimine to urea is 4.9:0.8, heating and boiling for 2 hours, adding 4 g of the mixed powder coated with magnesium hydroxide to the mixed solution, stirring for 72 hours, filtering, washing and drying.

[0064] Embodiment 13

[0065] The difference between Example 13 and Example 1 is that in Example 13, the post-treatment also includes the following steps: dissolving 2.5 g of polyethyleneimine and urea in 50 mL of water to form a mixed solution, the mass ratio of polyethyleneimine to urea is 5.2:1.2, heating and boiling for 2 hours, adding 5 g of the mixed powder coated with magnesium hydroxide to the mixed solution, stirring for 72 hours, filtering, washing and drying.

[0066] Embodiment 14

[0067] The difference between Example 14 and Example 12 is that in Example 14, the mass ratio of polyethyleneimine to urea is 4.9:0.2.

[0068] Embodiment 15

[0069] The difference between Example 15 and Example 12 is that in Example 15, the mass ratio of polyethyleneimine to urea is 4.9:1.8.

[0070] Detection Methods

[0071] The solid powder additive was prepared according to Example 1-15, and the flue gas temperature was 80°C and the initial flue gas sulfur dioxide concentration was 400 mg / Nm 3 The desulfurization efficiency of the solid powder additive was tested in low-temperature flue gas, and the results are recorded in Table 1;

[0072] Refer to the determination method in "GB / T30202.4-2013 Experimental method for coal-based granular activated carbon for desulfurization and denitrification Part 4: Desulfurization value", but after adsorption saturation, no thermal regeneration is carried out. Instead, the total sulfur content in the samples before and after desulfurization is determined, and the saturated sulfur capacity (in terms of SO2 mass percentage) is obtained by calculation, and the results are recorded in Table 1. The calculation formula is as follows: Saturated sulfur capacity = total sulfur content of the sample after desulfurization - total sulfur content of the sample before desulfurization.

[0073] Table 1 Desulfurization performance of solid powder additives

[0074] project Desulfurization efficiency / % Saturated sulfur capacity / %20-46 Example 1 91.01 42.9 Example 2 90.95 42.7 Example 3 91.05 43.2 Example 4 93.26 42.8 Example 5 93.67 43.0 Example 6 87.26 34.9 Example 7 86.95 35.2 Example 8 85.29 42.8 Example 9 85.31 42.9 Example 10 86.25 33.5 Embodiment 11 86.12 33.1 Example 12 95.12 47.2 Embodiment 13 95.31 46.8 Embodiment 14 92.35 43.1 Embodiment 15 92.12 43.2

[0075] According to Table 1 and Examples 1-3, it can be seen that the solid powder additives prepared in Examples 1-3 have good desulfurization efficiency and high saturated sulfur capacity. The solid powder additives prepared in Examples 1-3 include a composite adsorbent formed by zeolite and activated carbon and magnesium oxide, and the mixed powder is coated with magnesium hydroxide. Activated carbon and zeolite have a large specific surface area, which can effectively increase the contact area between the flue gas and the solid powder additive. Magnesium oxide and magnesium hydroxide, as magnesium-based desulfurizers, can absorb and fix acidic substances in the flue gas, such as sulfur dioxide and sulfur trioxide. The mixed powder formed by mixing and calcining magnesium oxide and the composite adsorbent has good strength and stable shape, and the magnesium oxide and the composite adsorbent are fully mixed, which effectively improves the desulfurization ability of the solid powder additive.

[0076] After the mixed powder is immersed in the magnesium chloride solution, the magnesium chloride penetrates into the mixed powder, and the sodium hydroxide solution is dripped, which can make the hydroxide react with the magnesium ion to generate magnesium hydroxide and precipitate, so that the mixed powder is uniformly precipitated with magnesium hydroxide, and the magnesium hydroxide can react with the sulfide to generate magnesium sulfite, etc., to achieve flue gas desulfurization treatment. The magnesium hydroxide layer precipitated in the post-treatment process is uniform and the thickness is adjustable, which effectively improves the desulfurization efficiency of the solid powder additive and simultaneously improves the saturated sulfur capacity of the solid powder additive.

[0077] Compared with Example 1-3, the desulfurization efficiency of the solid powder additive prepared in Example 4-5 is improved. During the preparation of the solid powder additive prepared in Example 4-5, the activated carbon is pretreated, and the activated carbon is activated at high temperature under nitrogen protection, which can effectively remove impurities in the activated carbon and have the effect of clearing the pores. At the same time, the specific surface area of ​​the activated carbon can be regulated, and the contact area between the flue gas and the solid powder additive is increased, thereby improving the absorption rate of the solid powder additive for sulfur-containing substances in the flue gas.

[0078] Compared with Example 1-3, the desulfurization efficiency of the solid powder additive prepared in Example 6-7 is reduced, and the saturated sulfur capacity is reduced. When preparing the solid powder additive prepared in Example 6-7, the mass ratio of the composite adsorbent to magnesium oxide is changed. The composite adsorbent can adsorb the flue gas and increase the contact area between the solid powder additive and the flue gas. Magnesium oxide can absorb sulfides such as sulfur dioxide in the flue gas. The mass ratio of the two affects the adsorption and reaction efficiency of the solid powder additive to the flue gas. The content of magnesium oxide decreases, and the flue gas adsorption and contact efficiency are higher. However, the reaction process of sulfides in the flue gas and magnesium oxide is slow. The content of magnesium oxide increases, and the flue gas adsorption efficiency is insufficient, which can easily lead to a decrease in desulfurization efficiency.

[0079] Compared with Examples 1-3, the desulfurization efficiency of the solid powder additive prepared in Example 8-9 is reduced. During the preparation of the solid powder additive prepared in Example 8-9, the mass ratio of zeolite to activated carbon was changed, indicating that the mass ratio of zeolite to activated carbon affects the adsorption effect of the composite adsorbent. Zeolite and activated carbon are compounded according to the mass ratio, which can make the composite adsorbent have a higher specific surface area, increase the contact area between the solid powder additive and the flue gas, and thus improve the adsorption performance of the solid powder additive.

[0080] Compared with Example 1-3, the desulfurization efficiency and saturated sulfur capacity of the solid powder additive prepared in Example 10-11 are decreased. When preparing the solid powder additive prepared in Example 10-11, the mass ratio of the mixed powder to magnesium chloride is changed. When the mass ratio of the mixed powder to magnesium chloride is decreased, the content of magnesium hydroxide coated on the surface of the solid powder additive is decreased, and the deposition amount of magnesium hydroxide is insufficient, thereby reducing the absorption capacity of the solid powder additive for sulfides. When the mass ratio of the mixed powder to magnesium chloride is increased, the deposition amount of magnesium hydroxide is excessive, causing partial pores of the composite adsorbent to be blocked, the specific surface area to be reduced, and the adsorption performance of the composite adsorbent to be reduced, thereby affecting the reaction rate of magnesium oxide and magnesium hydroxide with flue gas, and reducing the desulfurization efficiency and saturated sulfur capacity of the solid powder additive.

[0081] Compared with Examples 1-3, the desulfurization efficiency of the solid powder additive prepared in Example 12-13 is improved, and the saturated sulfur capacity is increased. During the preparation of the solid powder additive prepared in Example 12-13, the mixed powder coated with magnesium hydroxide is treated with urea and polyethyleneimine. The urea-based polymer generated by the reaction of urea and polyethyleneimine can be loaded on the surface of the mixed powder, so that the mixed powder contains more amino groups, and the amino groups can react with sulfides and fix them. Using urea and polyethyleneimine to treat the mixed powder can effectively improve the desulfurization efficiency and saturated sulfur capacity of the solid powder additive.

[0082] Compared with Examples 12-13, the desulfurization efficiency and saturated sulfur capacity of the solid powder additive prepared in Example 14-15 are decreased. During the preparation of the solid powder additive prepared in Example 14-15, the mass ratio of polyethyleneimine to urea is changed. The mass ratio of polyethyleneimine to urea directly affects the formation of urea-based polymers, which makes it easy for urea to decompose and volatilize, thereby reducing the amino content in the solid powder additive, thereby reducing the desulfurization efficiency and saturated sulfur capacity of the solid powder additive.

[0083] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A method for preparing a solid powder additive for flue gas desulfurization, characterized in that: The following steps are involved: (1) Preparation of composite adsorbent: After grinding and mixing activated carbon and zeolite, sodium carboxymethyl cellulose and polyvinyl alcohol are added, stirred until uniform, dried, extruded, and heat treated at 200-250°C for 1-1.2h to obtain a composite adsorbent; (2) Heat treatment: Grind and mix the composite adsorbent and magnesium oxide, and perform high-temperature calcination at a temperature of 700-850°C for 1-2 hours to obtain a mixed powder; (3) Post-treatment: coating the mixed powder with magnesium hydroxide, adding the mixed powder to an alcohol solution of magnesium chloride, adding a dispersant, ultrasonically shaking for 30 minutes, adding an alcohol solution of sodium hydroxide at 60°C while stirring, stirring and reacting for 18 hours after the addition is completed, washing, and drying to obtain a solid powder additive; the post-treatment also includes the following steps: dissolving polyethyleneimine and urea in water to form a mixed solution, heating and boiling for 2 hours, adding the mixed powder coated with magnesium hydroxide to the mixed solution, stirring for 72 hours, filtering, washing, and drying.

2. The method for preparing a solid powder additive for flue gas desulfurization according to claim 1, characterized in that: The activated carbon is treated as follows before being mixed with the zeolite: the activated carbon is dried at 100-105°C for 24 hours, nitrogen is introduced, the temperature is raised to 450-500°C and kept for 1 hour, and then cooled to room temperature.

3. The method for preparing a solid powder additive for flue gas desulfurization according to claim 1, characterized in that: The mass ratio of the composite adsorbent to magnesium oxide is (0.4-0.6):(0.4-0.6), and the mass ratio of activated carbon to zeolite is (1-1.2):(0.9-1.1).

4. The method for preparing a solid powder additive for flue gas desulfurization according to claim 1, characterized in that: The mass ratio of the mixed powder that has not been coated with magnesium hydroxide to magnesium chloride is (1.3-1.7):(4.4-4.9).

5. The method for preparing a solid powder additive for flue gas desulfurization according to claim 1, characterized in that: The mass ratio of the polyethyleneimine to urea is (4.9-5.2):(0.8-1.2).

6. A solid powder additive for flue gas desulfurization, characterized in that: The solid powder additive for flue gas desulfurization is prepared by the preparation method of any one of claims 1-5.

Citation Information

Patent Citations

  • Supported hydroxide high-selectivity gasoline adsorption deep desulfurizing agent and preparation method thereof

    CN108187605A

  • Novel efficient desulfurizing agent and preparation method thereof

    CN110893312A